Retrospective SARS-CoV-2 human antibody development trajectories are largely sparse and permissive - Monica B. Kirby; Brian M. Petersen; Jonathan G. Faris; Siobhan P. Kells; Kayla G. Sprenger; Timothy A. Whitehead (Proceedings of the National Academy of Sciences, 2025)
Immunological interventions, like vaccinations, are enabled by the predictive control of humoral responses to novel antigens. While the development trajectories for many broadly neutralizing antibodies (bnAbs) have been measured, it is less established how human subtype-specific antibodies develop from their precursors. In this work, we evaluated the retrospective development trajectories for eight anti-SARS-CoV-2 Spike human antibodies (Abs). To mimic the immunological process of BCR selection during affinity maturation in germinal centers (GCs), we performed deep mutational scanning on anti-S1 molecular Fabs using yeast display coupled to fluorescence-activated cell sorting. Focusing only on changes in affinity upon mutation, we found that human Ab development pathways have few mutations which impart changes in monovalent binding dissociation constants and that these mutations can occur in nearly any order. Maturation pathways of two bnAbs showed that while they are only slightly less permissible than subtype-specific Abs, more development steps on average are needed to reach the same level of affinity. Many of the subtype-specific Abs had inherent affinity for antigen, and these results were robust against different potential inferred precursor sequences. To evaluate the effect of differential affinity for precursors on GC outcomes, we adapted a coarse-grained affinity maturation model. This model showed that antibody precursors with minimal affinity advantages rapidly outcompete competitors to become the dominant clonotype.